(untitled) (Regional aspects of productive forces development of Ukraine, 2023)
Introduction. The article examines the issue of the hydroecological state of water resources of Ukraine in a regional section. The situation and trends in the field of water supply, some aspects of financing, administrative and management vectors in this field are characterized. The need to implement a set of measures to improve the ecological situation, optimize approaches to nature use, preservation and protection of hydroecosystems is emphasized. The purpose of the article is to study the hydro-ecological state of water resources, factors affecting water quality, approaches to the protection of hydro-ecosystems at the regional level (on the example of the Ternopil region). Research methods. The methods of analysis and synthesis, systematic generalization were used in the preparation of the scientific publication. Results: Ukraine’s water resources require comprehensive measures to improve their ecological status, optimize approaches to nature management and protection. An analysis of the ecological problems of the hydroecosystems of the Ternopil region was carried out, and the main reasons for their degradation were clarified. Installed. the satisfactory state of water bodies and the main areas of work to improve the ecological state of the region’s rivers are recommended. It is necessary to clear the riverbeds, optimize the industrial and communal water treatment system, establish and expand sanitary protection zones, strengthen the banks, stimulate the responsible attitude of the population and individuals to the preservation of water bodies and the improvement of their condition through environmentalization, education and financial regulation mechanisms , implement measures to prevent unauthorized interference in channel processes, increase funding for the restoration of water resources with strict control of the expenditure part and strict reporting.